Influence of natural convection on the electrodeposition of copper nanowires in anodic aluminium oxide templates. (10th February 2023) - Kalinin, I.A.; Davydov, A.D.; Leontiev, A.P.; Napolskii, K.S.; Sobolev, A.; Shatalov, M.; Zinigrad, M.; Bograchev, D.
Abstract: Templated electrodeposition is a versatile method for preparing metal nanostructures. Among the various parameters of this process, the effect of convection on the deposition process is less explored. The present work is devoted to the experimental and theoretical study of the influence of natural convection near nanoporous anodic aluminium oxide templates on the deposition of nanowires. Electrochemical deposition of copper nanowires was carried out with vertical templates parallel to the gravitational acceleration at various overpotentials. A model of nanowire electrodeposition was developed based on the Navier‒Stokes and diffusion equations. The length profiles of the nanowires, experimentally measured using scanning electron microscopy, were compared with the results of the numerical simulation. The simulation results were also compared with current-time transients recorded during metal electrodeposition into nanopores. In addition, an analytical expression has been proposed to describe the evolution of the deposition current density into nanopores under natural convection conditions.